An investigation of teachers' experiences of a Geoboard intervention programme in area and perimeter in selected Grade 9 classes: a case study - Mkhwane, Fezeka Felicia (Rhodes University, Faculty of Education, Department of Education, 2018)
The study was undertaken with three Grade 9 teachers at three selected schools which are part of RUMEP's Collegial Cluster Schools' programme that I coordinate. Collegial clusters are communities of teachers who aim at improving their practice by working on their own professional development. The purpose of this study was to investigate the selected Grade 9 teachers' experiences of a Geoboard intervention programme. It also wanted to investigate the role that a Geoboard can play in the teaching and learning of area and perimeter of two-dimensional shapes. The research was a case-study within the interpretive paradigm. A variety of data collection techniques was used. These included baseline assessment tasks, observations during the intervention programme, post intervention assessment tasks and semistructured interviews with the participating teachers and a few learners from each participating school. The collected data was analysed using both the quantitative and qualitative methods. My research findings reveal that a Geoboard, as a manipulative, developed confidence in the participating teachers. In the interviews with teachers, it transpired that teachers' skills in teaching area and perimeter of two-dimensional shapes had been sharpened. According to the interviews with learners, the use of a Geoboard led to better conceptual understanding of the area and perimeter, as learners no longer had to rely on formulae. Kilpatrick et al. (2001) refer to conceptual understanding as an integrated functional grasp of mathematical ideas. The post intervention assessment task showed a positive shift in learners' performance. The average learner performance improved from 29% in the baseline assessment task to 61% in the post intervention assessment task. This shows that the use of a Geoboard led to meaningful learning of area and perimeter of two-dimensional shapes. The overall research findings reveal that the use of manipulatives has a positive impact in the teaching and learning of area and perimeter. Learners' responses to the interview questions showed that there was better understanding of the two concepts, which enabled them to construct their own knowledge. They further said the Geoboard allowed them to be hands-on, which contributed to their active involvement in the lesson.
Keywords: Mathematics -- Study and teaching (Secondary) -- South Africa; Teachers -- Training of -- South Africa; Manipulatives (Education); Effective teaching; Area measurement; Perimeters (Geometry); Problem solving -- Study and teaching; Geoboard Intervention Programme; RUMEP